Evolution of management strategies for unstable pelvic ring injuries over the past 40 years: a systematic review - Kenichi Sawauchi; Luca Esposito; Yannik Kalbas; Zygimantas Alasauskas; Valentin Neuhaus; Hans-Christoph Pape; Felix Karl-Ludwig Klingebiel; Roman Pfeifer (Patient Safety in Surgery, 2024)
Abstract Background Hemodynamically unstable pelvic ring fractures from high-energy trauma are critical injuries in trauma care, requiring urgent intervention and precise diagnostics. With ongoing advancements in trauma management, treatment strategies have evolved, with some techniques becoming obsolete as new ones emerge. This study aimed to evaluate changes and trends in treatment algorithms for these injuries over approximately 40 years. Methods A systematic review of PubMed and EMBASE was conducted to include articles published over roughly four decades that presented visual treatment algorithms or workflows for managing unstable pelvic ring fractures. Identified algorithms were categorized by publication period and analyzed by initial assessment, diagnostic methods, pelvic stabilization, and hemorrhage control interventions. Results The search identified 5,434 publications, of which 32 met the inclusion criteria. 75% of these studies were published between 2011 and 2022, reflecting a growing focus on standardization, particularly in Europe, North America, and Asia. Physiological assessment remains essential in the initial management of hemodynamically unstable pelvic ring fractures, guiding resuscitation and influencing the selection of intervention and imaging. The use of pelvic binders or sheets has risen steadily, highlighting their role in hemorrhage control and temporary stabilization. CT scans and angiography have largely replaced pelvic X-rays in diagnostic protocols, becoming preferred radiological methods alongside focused assessment with sonography for trauma (FAST). Pelvic stabilization remains critical, with external fixation being the most commonly used technique, showing an upward trend in recent years. Laparotomy, pelvic packing, and angioembolization continue to play vital roles in hemorrhage management. Emerging techniques, such as resuscitative endovascular balloon occlusion of the aorta (REBOA), anterior subcutaneous internal fixation (INFIX), and rescue screws, are increasingly included in treatment algorithms, while diagnostic peritoneal lavage (DPL) has become obsolete and is no longer listed in these algorithms. Conclusions This review provides foundational insights toward the standardization of initial treatment for hemodynamically unstable pelvic ring fractures and holds significant importance in enhancing the consistency and efficiency of treatment. Future research should focus on accumulating higher-quality evidence to evaluate the effectiveness of standardized protocols and explore the applicability of new treatment methods.